Travel thru history. Discover Toronto [videorecording (DVD)] (Travel thru history., 2019)
Viewers visit the world class city of Toronto. There they'll head straight up the Western Hemisphere's tallest structure, the CN Tower. Next we score a look at the Hockey Hall of Fame and see a North American castle at Casa Loma. Finally they see how the British defended the city of York against the newly formed United States at Fort York.